Estágios imaturos de Lepidoptera e parasitoides associados, em fragmento de mata semidecidual em São Carlos, Estado de São Paulo - Iemma, Luis Gustavo Rodrigues (2010)
A semidecidual forest fragment located in Parque Eco-Esportivo Damha, São Carlos, SP, was studied. The purpose was to sample the diversity of Lepidoptera larvae, their host plants and associated parasitoids. Five different plant species were sampled during 13 months using an entomological umbrella; 266 larvae belonging to 11 families and 26 genera were obtained. The most abundant family was Geometridae, with 32.81% of total amount, followed by Nymphalidae and Gelechiidae. The most abundant genus was Eois (Geometridae) with 28.20% of total larvae amount. The major occurrence of larvae was between the end of raining period and the beginning of the dry period. Using the saturation curve is observed that the survey was not sufficient to sample the real diversity of larvae of this forest fragment. During the work, 10% of larvae were parasitized and a total of 907 parasitoids emerged from different hosts, all koinobionts. Tachinidae was the most frequent parasitoid registered and occurred on Quadrus sp.; The most abundant parasitoid in number of specimens was Copidosoma sp. Polyembrionic parasitoid, attended by 787 found on Plusiinae (Noctuidae).